A Hidrodinâmica para o ensino médio na perspectiva da aprendizagem significativa. - Lima, Antonio Vilemar Bezerra (2019)
The objective of this work was to teach the content of hydrodynamics contextualized in a stand-ard system of basic sanitation, for students of the 1st year of high school. The fundamental idea that governed this work was the need to fill this gap in secondary education by inserting the hydrodynamic theme and emphasizing its relevance in the general context of the subjects of mechanics and, especially in the daily life of students, within a scenario in the teaching of Physics that does not prioritize this theme. It is based on Ausubel's meaningful learning theory. Before starting the research with the students, a questionnaire was applied with 30 Physics teachers in order to find out if the content of Hydrodynamics is approached by them in their classrooms. The research with the students began with the presentation of the content and application of a previous questionnaire that had as objective, to identify the previous knowledge of the students related to Hydrodynamics. Next, a didactic sequence was composed of six pedagogical moments consisting of lectures with audio-visual resources, where, in addition to the basic knowledge of hydrodynamics, the hydrological cycle in nature was described, the steps of a standard system of basic sanitation , divided into two parts: water supply and sanitary sewage, in some stages were developed experiments with low cost materials. Continuing the pedagogical moments of the research, two videos on Hydrodynamics were presented and a questionnaire on videos was applied. To finalize the moments with the students, a new questionnaire was applied. After the pedagogical sequence described, we collected, classified and analyzed the results obtained from the students' answers to the research questionnaires. To finalize this work, a proposal was presented for an educational product to be applied in secondary schools.